2008
DOI: 10.1177/107769900808500108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Journalists' Perceptions of Media Impact

Abstract: H o w journalists perceive media influence was explored by comparing resultsfrom a survey of Israeli journalists (n = 200) and a survey of the Israeli adult population (n = 2,203). As predicted, journalists demonstrated signifcant third-person perceptions (TPPs), but these were acfually smaller than those of the public. Journalists tended more than the public to perceive media influence as positive. Journalists perceiving a stronger media influence were relatively new journalists and worked for local media, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
1
11
0
3
Order By: Relevance
“…Which media influences are being regarded as favourable or positive and which as negative? Journalists´ answers to this question might differ from those of other people (see Tsfati & Livio, 2008). This is decisive in order to determine whether strong or weak media influences are the more favourable option for the own country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which media influences are being regarded as favourable or positive and which as negative? Journalists´ answers to this question might differ from those of other people (see Tsfati & Livio, 2008). This is decisive in order to determine whether strong or weak media influences are the more favourable option for the own country.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies mainly observed similarities in journalists´ and other respondents´ presumptions of the strength of media influences on the public. Only judgments about media influence on self (Tsfati and Livio, 2008) and media influences for one special topic of coverage (Dohle and Vowe, 2010) differed significantly between journalists and the control groups. This means there is no reason to believe that journalists, despite their professional involvement with the media, should not exhibit third-person perceptions in a similar way as other people.…”
Section: Patterns Of An International Third-person Perception In Newsmentioning
confidence: 92%
“…Couldry and Curran (2003, p. 4) state that media power is not "made explicit by those who benefit from it". Such distortions in reporting media power perceptions show that media power and its perception form a complex relational concept, and that political communication elites mainly assert their tenuous relationship with the concept of media power (Tsfati and Livio, 2008).…”
Section: The Concept Of Media Power In Politicsmentioning
confidence: 99%
“…More recent research investigates journalists' third-person perceptions, i.e., the difference between presumed strength of media influence on self and others (Bernhard & Dohle, 2014;Dohle & Vowe, 2010;Tsfati & Livio, 2008). These studies are designed as quasi-experiments and test for differences in third-person perceptions between journalists and other groups of people.…”
Section: Dimensions Of Journalists' Presumptions About Media Effectsmentioning
confidence: 99%